Direct Cost of Maternity-care Services in South Delhi: A Community Survey - Dhar, Rinku Sen Gupta; Nagpal, Jitender; Sinha, Swati; Bhargava, VL; Sachdeva, Aarti; Bhartia, Abhishek (Journal of Health, Population and Nutrition, 2009)
The study was conducted to estimate the direct maternity-care expense for women who recently delivered in South Delhi and to explore its sociodemographic associations. A survey was conducted using the two-stage cluster-randomized sampling technique. Two colonies each from high-, middle- and low-income areas were selected by simple random sampling, followed by a house-to-house survey in each selected colony. Information was collected by recall of healthcare expenses for mother and child. In total, 249 subjects (of 282 eligible) were recruited. The mean expense for a normal vaginal delivery (n=182) was US 370.7, being much higher in a private hospital (US 1,035) compared to a government hospital (US 61.1) or a delivery in the home (US 55.3). Expenses for a caesarean delivery (n=67) were higher (US 1,331.1). Expenses for the lowest-income groups were 10% of their annual family income at government facilities and 26% at private hospitals. The direct maternity expense is high for large subsections of the population. Key words: Community survey; Healthcare cost; Health expenditure; Maternal health services; Maternity care; India doi: 10.3329/jhpn.v27i3.3379 J Health Popul Nutr 2009 Jun;27(3):368-378